Um estudo de escalonamento UPLINK considerando a camada física OFDM do padrão IEEE 802.16 - Oliveira, Antônio Neco de (2011)
The IEEE 802.16 standard denes the specications for the medium access control layer (MAC) and the parameters for the physical layer (PHY), which allow to structure an architecture for providing Quality of Service (QoS) in the broadband wireless access networks [1, 2]. However, it leaves open how to implement policies to meet the QoS requirements of user applications, so as to enable manufacturers to dierentiate their products to this standard. This work, aim a more realistic analysis of the uplink scheduling mechanism, based on discipline Priority Queue (PQ), taking into account the parameters of the OFDM (Orthogonal Frequency Division Modulation) physical layer specied in IEEE 802.16. To do so, it extends the WiMAX module for the uplink scheduling mechanism that considers the value of the signal-to-noise ratio (SNR) shown in the subscriber station (SS) and allow selection of a modulation and coding scheme (MCS) according with the characteristics of wireless communication channel. Thus, an MCS which produces an OFDM symbol more resistant to interference of the physical environment, the transmitted signal will achieve greater distance between the SS (Subscriber Station) and BS (Base Station), while the eficient MCS will allow for more eective data rate for the communication channel, encoded more data bits per OFDM symbol. This work has been evaluated using the simulation tool NS-2 (Network Simulator, version 2) with the simulation module for WiMAX networks extended this work to allow more realistic results.